Polarimetric micro-doppler signature measurement of a small drone and its resonance phenomena. Issue 11 (24th July 2021) - Kim, Sangin; Lee, Hyunjae; Noh, Yeong-Hoon; Yook, Jong-Gwan
Abstract : This study presents the micro-Doppler signature (MDS) of small drones based on resonance phenomena. The MDS analysis of a drone is conducted for various detection conditions. The Doppler frequencies due to the rotation of rotor blades, characterized by different materials and dimensions, are extracted at specific angular frequencies. It is confirmed that the resonance phenomenon caused by the copper-coated conducting rotor blade significantly affects the Doppler frequency. As the rotor blade dimension increases, the resonance effect moves to a lower frequency band. It is interesting to note that the resonance effect of horizontal to horizontal (HH) polarization occurs in a lower frequency band compared to vertical to vertical (VV) polarization. Additionally, it is performed in a monostatic and bistatic radar environment to analyze the resonance effect. The theoretical analysis based on full-wave simulation is confirmed via measurements with frequency-modulation continuous wave (FMCW) radar.